Gestión logística y su impacto en la calidad de servicio de la empresa disebaj s.a cantón Quevedo año 2023 - Vera Aspiazu, Omar Alexander (2025)
This research aimed to analyze the impact of logistics management on service quality at Disebaj S.A., a company located in the Quevedo canton, in 2023. A mixed approach with descriptive and correlational scope was applied. Data collection was conducted through a survey of a census sample of 120 customers and structured interviews with the company's logistics staff. These instruments were used to analyze key indicators such as delivery time compliance, customer satisfaction, service delivery, and delivery delays. The survey results revealed that only 30.83% of customers perceived deliveries to be on time, while 52.58% expressed satisfaction with the service received. An intermediate level of service delivery was also identified, reflected in neutral perceptions of the reliability and tangibility of the logistics process. The interviews identified internal challenges such as a lack of route planning, deficiencies in inventory management, and limited process automation. Guidelines were proposed to optimize logistics management, including process digitization, human talent training, and strengthening customer communication channels. It was concluded that the logistics weaknesses detected directly impact customer perception and limit the scope of a satisfactory service experience. Therefore, concrete actions are required to strengthen internal processes and improve the quality of the service offered.